Constructing Digital Patriarchy: Framing the Hadith of Dayyūth and Gendered Morality in Online Islamic Discourse - Rohmah, Nur Maulidya Wardatur; Mukhammad Zamzami; Ida Rochmawati (Journal of Ushuluddin and Islamic Thought, 2025)
This article analyzes the construction of digital patriarchy in Islamic moral discourse through the use of hadith about dayyūth on the Instagram account @mahasiswa.salaf using Robert N. Entman's Framing Analysis framework. In the context of social media as a space for contesting religious authority, this hadith not only functions as a source of family ethics but also as an ideological instrument that shapes moral boundaries and gender relations. Through Entman's four dimensions, such as problem definition, diagnosis of causes, moral judgment, and treatment recommendation, this article shows that the account defines moral threats as the result of men's negligence in protecting family honor, judges such behavior as a sin that blocks the path to heaven, and recommends male control over women as a solution. These findings reveal that religious narratives in digital spaces reinforce patriarchal hegemony through textual legitimation, but also open up space for resistance through audience interactions that challenge conservative interpretations with arguments for gender equality. This article contributes to the study of digital religion and Islamic gender studies by emphasizing the need for a reinterpretation of hadith based on social ethics that emphasize collective moral responsibility, the value of raḥmah, and justice in an increasingly ideological and fragmented digital religious ecosystem.